Instilling and Fostering a Sense of Community through Inclusive Security and Development - Kabir, Md Humaoun; Uddin, Helal (Society & Sustainability, 2024)
Community security and development face significant challenges because of many factors like corruption, social divisions, and economic inequality. Such factors impede the building of a cohesive and resilient community through weakening social bonds and mutual trust. This study examines how inclusive security and development can foster a sense of community by enhancing shared interests, peace, and identity. It employs a qualitative research approach depending solely on secondary data. This descriptive research collects data from secondary sources like books, journal articles, newspaper articles, blog writings, and websites. The findings of this study suggest that addressing inclusive security and development together contributes significantly to building stronger community ties, enhanced social cohesion, and a sense of belongingness. It also argues that a safe and cohesive community environment promotes social collaboration and harmony. This paper recommends emphasizing inclusive approaches in the security and development process to ensure equal access to resources and a favorable climate for peaceful coexistence.